Waldron and dignity: The problem of the basis of human rights - Chávez-Fernández Postigo, José Carlos (2020)
Since no more than ten years Jeremy Waldron has been working on a legal and philosophical conception of dignity that conceives it mainly as «rank» or «status», and that understands it —not exclusively, but significantly— as the basis of human rights. This approach is proposed as an alternative to the rival conceptions of dignity that are currently found in legal scholarship and in the rulings of high courts, such like the Kantian, the Roman-Catholic and the Dworkinian. This work will try to prove that, despite its great hints, the Waldron’s thesis about dignity has at least three relevant problems which arise from the insufficient clarification of what he calls the «underlying idea» of human dignity, which I will classify as: that of «weakness», that of «harmonization-determination», and that of «secularity». The goal will be to show that it is possible to test a conception of Waldron’s «underlying idea» of human dignity that, resorting to an Aristotelian notion of human nature and without renouncing to the positive features of Waldron’s approach, overcomes successfully the problems mentioned.